Oxygen and trace elements (Mn/Ca ratio) collected in Anholt, Hano Bay and Gullmar fjord from Groeneveld et al., (2018) and Groeneveld and Filipsson (2013) - Mattia Ferraro; Bjørg Risebrobakken; Irina Polovodova Asteman; Elin Darelius; Amandine Tisserand; Natalya Gallo; Anne Gro Vea Salvanes (PANGAEA, 2025)
Oxygen (umol/kg) and trace elements (Mn/Ca ratio) from Groeneveld et al., (2018) and Groeneveld and Filipsson (2013). We used oxygen of seawater to calculate oxygen saturation and the Apparent Oxygen Utilisation (AOU) using the gsw_O2sol toolkit for python.
In: Ferraro, M et al. (2025): Dissolved oxygen concentration, trace elements concentration, carbon isotope composition and foraminifera assemblages data from Western Norwegian fjords [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982538